Transformation Of Social And Economic Livelihoods Of Rubber Farmers - Muh Fajrin Kasdi (EcceS (Economics, Social, and Development Studies), 2020)
Rubber production in Bulukumba Regency continues to increase the amount of production every year, to be precise in Bulukumpa District, Batulohe Village. But in fact, the life of rubber farmers is still very far from prosperous. The novelty of this research is to try to capture the livelihoods of rubber farmers from sociological and economic aspects. The purpose of this study was to determine the structure of land tenure, wage levels, education levels, access to information, and trade value chains in Batulohe Village, Bulukumpa District. This research was conducted in Batulohe Village, Bulukumpa District, Bulukumba Regency. This type of research is qualitative ethnographic in nature, this model seeks to study cultural events, which present the subject's view of life as an object of study. The data source of this research comes from direct interviews with rubber farmers. Data processing and data validation techniques used were source triangulation techniques to test the validity of the information obtained from informants. The results showed that there was no imbalance in land tenure structure because in fact the community already owned land. The level of wages given to farm laborers is not proportional because it does not follow the prevailing rubber price trend. The education level of farmers is still relatively low. Meanwhile, existing access to information is not transparent and unequal because it is monopolized by traders at both the village and city levels. Finally, the trade chain that occurs involves several actors, starting from farmers, village traders, urban traders to the processing industry, which tends not to benefit farmers. A big push intervention policy from the government is needed so that there will be a redistribution of fiscal allocations to the poor and an improvement in livelihoods and income. Keywords: Rubber Farmers, Social Economic; Welfare.